Toward a Low-Carbon Economy : Renewable Energy and Energy Efficiency Portfolio Review - World Bank (Washington, DC, 2014)
Renewable energy and energy efficiency projects continue to perform strongly in the World Bank Group (WBG) energy portfolio and are increasingly being mainstreamed in the WBG's energy lending. In fiscal 2007 a total of US$1,433 million supported 63 renewable energy and energy efficiency projects in 32 countries. In addition to operational activities, the WBG engages in a variety of economic sector work and technical assistance focused on renewable energy and energy efficiency. This work is an integral part of the WBG activities, which is valued as an important source of information and advice for policy makers and other stakeholders. In addition, these activities are an important component in the preparation of future lending activities. The Energy Sector Management Assistance Program (ESMAP) is a multi-donor trust-funded global technical assistance program that has reached its 25th anniversary. This program provides policy advice on sustainable energy development to governments of developing countries and economies in transition. The carbon finance project aims at promoting investments in wind energy to reduce greenhouse gas emissions, to contribute to the further development of the international carbon market in Mexico through the supply of emissions reductions under the clean development mechanism and to improve energy security.